(untitled) (BIRDEM Medical Journal, 2021)
Cushing syndrome results from chronic exposure to excess cortisol. Nodular adrenal hyperplasia is usually bilateral and has only a few case reports of unilateral presentation. Biochemically it is presented as hyperaldosteronism or as Cushing’s syndrome. Here, we are reporting a 17-year-old female presenting with weight gain over 5 months and uncontrolled hypertension. Biochemically she was found to have diabetes mellitus, secondary hypothyroidism and hypogonadotrophic hypogonadism due to Cushing’s syndrome of adrenal origin. Unilateral adrenal adenoma/hyperplasia in right adrenal gland was evident by radiology. Histopathological examination was done after laparoscopic adrenalectomy showed nodular adrenocortical hyperplasia in right adrenal mass. Following surgery, clinical features of the patient improved notably. Cushing syndrome due to unilateral nodular adrenocortical hyperplasia is a rare entity. Biochemical evaluation of hypothalamo-pituitary-adrenal axis, radiological evidence and histopathology are the important armaments can guide to final diagnosis. BIRDEM Med J 2022; 12(1): 78-82